2017
DOI: 10.22159/ijpps.2017v9i6.16851
|View full text |Cite
|
Sign up to set email alerts
|

Design, Formulation and in Vitro Drug Release From Transdermal Patches Containing Imipramine Hydrochloride as Model Drug

Abstract: Objective: The aim of the present investigation was to form matrix type transdermal patches containing imipramine hydrochloride were prepared using two polymers by solvent evaporation technique to minimise the dose of the drug for lesser side effect and increase the bioavailability of a drug. Methods:In the present study, drug loaded matrix type transdermal films of imipramine hydrochloride were prepared by the solvent evaporation method with the help of polymers along with polyethene glycol (PEG) 400 was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
(15 reference statements)
1
18
0
Order By: Relevance
“…Formulation batches F1 to F3 gave higher percentage cumulative drug release because they had a higher proportion of hydrophilic polymer as compared to formulation batches F4 to F6. The same result with hydrophilic polymers is also obtained by Hardainiyan et al [19] and Sadhasivam et al [20]. High polymer content in patches provides faster polymer matrix dissolution in aqueous media thus give higher drug release.…”
Section: Folding Endurancesupporting
confidence: 81%
“…Formulation batches F1 to F3 gave higher percentage cumulative drug release because they had a higher proportion of hydrophilic polymer as compared to formulation batches F4 to F6. The same result with hydrophilic polymers is also obtained by Hardainiyan et al [19] and Sadhasivam et al [20]. High polymer content in patches provides faster polymer matrix dissolution in aqueous media thus give higher drug release.…”
Section: Folding Endurancesupporting
confidence: 81%
“…The in vitro permeation experiment indicated that when the hydrophilic polymer concentration increased, the amount of drug permeation increased. As described by Rao and Diwan, initial rapid dissolution of the hydrophilic polymers occurs when the patch is in contact with the hydrated skin, resulting in the accumulation of high amounts of the drug on the skin surface and thus leading to the saturation of the skin with drug molecules at all times [20,22].…”
Section: Fig 1: Dsc Thermograms Of Drugs Polymers and The Physicalmentioning
confidence: 99%
“…The donor chamber comprises a plastic ring (1) to which is attached a membrane sac (2), such that the interior of the plastic ring and the open end of the membrane sac are in flow communication with each other. This semi-permeable membrane could be replaced by animal's skin or, any other cellular membrane.…”
Section: Donor Chambermentioning
confidence: 99%
“…Among the drug delivery systems, transdermal drug delivery offers avoidance of first-pass metabolism, decreased toxicity, fewer side effects, as well as greater patient compliance [1,2]. To evaluate the performance of prepared transdermal formulation in vitro static diffusion cells are used.…”
Section: Introductionmentioning
confidence: 99%